NON-INVASIVE DETERMINATION OF LIQUID DIFFUSION COEFFICIENTS USING LASER BEAM DEFLECTION AND REFRACTIVE INDEX GRADIENTS: A STUDY ON NaCl - Handoko, Djati; Hifzhi, Affan; Sudarmaji, Arief; Dewi, Fitria Yunita (Indonesian Physical Review, 2025)
This research describes and verifies the creation of a straightforward system for determining liquid diffusion coefficients using the Laser Beam Deflection (LBD) technique for measuring diffusion rates in sodium chloride solutions. The system exploits refractive index gradients that develop during diffusion to produce a detectable laser beam deviation, which is subsequently analyzed to calculate diffusion coefficients. Our experimental setup, which builds on Wiener's original design with several improvements, consists of a laser source with a cylindrical lens, a diffusion cell, and a screen for capturing projected images. We conducted an in-depth analysis of time-dependent measurements (5, 20, and 45 minutes), concentration variations (20/100, 25/100, and 30/100 NaCl/aquades ratios), and geometric configurations (30°, 45°, and 60° tilt angles) and found that the initial diffusion coefficients exhibit time-dependent behavior before stabilizing at approximately.  Within the examined range, concentration had a negligible impact on diffusion coefficients, but the geometric orientation had a substantial effect on measurement accuracy, resulting in a measurement error of approximately 3.00% when the configuration was set at 45°. Linear correlations between the natural logarithm of the ratio of the concentration difference to time, and the inverse square of the height, were found to be consistent with Fick's second law of diffusion under all tested conditions. This non-invasive approach offers a dependable substitute for conventional methods of diffusion measurement, which may be utilised in fields such as solution chemistry, food science, and pharmaceutical formulations.